Purification and characterization of an exopolysaccharide of Burkholderia (Pseudomonas) pseudomallei. - Steinmetz, I (1995)
Burkholderia pseudomallei (basonym Pseudomonas pseudomallei) is the causative organism of melioidosis, a disease which is recognized as a major public health problem primarily in Southeast Asia and Northern Australia. In this paper, we report on the identification, purification, and characterization of a species-specific exopolysaccharide of B. pseudomallei. After immunization of mice with a B. pseudomallei strain exhibiting mucoid growth characteristics, we isolated an immunoglobulin G1 monoclonal antibody (MAb) (3015) with specificity for a carbohydrate structure as determined by immunoblotting following sodium dodecyl sulfatepolyacrylamide gel electrophoresis. Electron microscopy studies with MAb 3015 revealed reactivity with an exopolysaccharide with a capsule-like appearance in the immunizing strain. All of the mucoid and nonmucoid B. pseudomallei strains tested from geographically different tropical regions were recognized by MAb 3015 in an enzyme-linked immunosorbent assay or immunoblot, indicating that the exopolysaccharide is constitutively expressed among this species. Intensive testing for cross-reactivity including members of all the Pseudomonas rRNA groups showed no cross-reactivity except in the case of the closely related species Burkholderia mallei. A protocol for purification of the exopolysaccharide which is based principally on mechanical separation from the cell surface followed by repetitive ethanol precipitation steps and finally affinity chromatography using MAb 3015 was established. The exopolysaccharide yielded was of high purity. Gel permeation chromatography was performed, and the molecular mass was estimated to be > 150 kDa. Sera from patients with melioidosis were strongly reactive with the purified exopolysaccharide, indicating its in vivo expression and immunogenicity in natural infection. The diagnostic value of the exopolysaccharide and its role in the pathogenesis of disease must still be determined.